7.7% Efficient All‐Polymer Solar Cells. (2nd July 2015) - Hwang, Ye‐Jin; Courtright, Brett A. E.; Ferreira, Amy S.; Tolbert, Sarah H.; Jenekhe, Samson A.
<x xml:space="preserve">Abstract</x> By controlling the polymer/polymer blend self‐organization rate, all‐polymer solar cells composed of a high‐mobility, crystalline, naphthalene diimide‐selenophene copolymer acceptor and a benzodithiophene‐thieno[3, 4‐b]thiophene copolymer donor are achieved with a record 7.7% power conversion efficiency and a record short‐circuit current density (18.8 mA cm−2).